2015
DOI: 10.1038/nphys3594
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of spin–orbit coupling in iron-based superconductors

Abstract: Spin-orbit coupling (SOC) is a fundamental interaction in solids which can induce a broad spectrum of unusual physical properties from topologically non-trivial insulating states to unconventional pairing in superconductors. In iron-based superconductors (IBS) its role has so far been considered insignificant with the models based on spin-or orbital fluctuations pairing being the most advanced in the field. Using angle-resolved photoemission spectroscopy we directly observe a sizeable spin-orbit splitting in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
198
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(220 citation statements)
references
References 44 publications
21
198
1
Order By: Relevance
“…ARPES measurements (Ref. [21]) extracted λ ∼ 10−20meV, comparable to µ. Without SO, the Cooper states at zero momentum can be classified according to their behavior separately under the crystal's point group operations and under spin SU (2) rotations.…”
Section: Pacs Numbersmentioning
confidence: 99%
See 1 more Smart Citation
“…ARPES measurements (Ref. [21]) extracted λ ∼ 10−20meV, comparable to µ. Without SO, the Cooper states at zero momentum can be classified according to their behavior separately under the crystal's point group operations and under spin SU (2) rotations.…”
Section: Pacs Numbersmentioning
confidence: 99%
“…The renormalization affects differently the prefactors in different terms in Eq. (21). In a generic case, H b changes to…”
Section: Supplementary Materials a Pairing In The Orbital And Bandmentioning
confidence: 99%
“…It has been shown that single electron spinorbit coupling in iron-based superconductors is strong 27 (approximately 10.7 meV), and neutron scattering experiments suggest that this single electron spinorbit coupling reveals itself in the magnetic excitation spectrum; a spin-space anisotropy exists to around 6-8 meV 28,29 . Additionally, our density-functional-theory calculations, discussed in Sec.…”
Section: Magnetic Structuresmentioning
confidence: 99%
“…As the system is doped towards its maximum superconducting transition temperature, both gaps decrease 16 . Meanwhile, an atomic-like spin-orbit coupling present in the system gives rise to splittings at the Γ point of the order of 10-30 meV in the band structure 17 without any broken-symmetry 13 .…”
Section: Introductionmentioning
confidence: 99%